Red electroluminescence from Tb2O3: Eu/PEDOT: PSS heterojunction light-emitting diodes. (October 2020) - Wan, Guangmiao; Wang, Shenwei; Li, Ling; Yin, Xue; Mu, Guangyao; Yi, Lixin
Abstract: In this work, heterojunction light-emitting diodes made of Tb2 O3 : Eu and PEDOT: PSS were prepared and the impact of PEDOT: PSS on luminous intensity of the devices was studied. The electrical and optical properties of the devices were tested. Five luminescence peaks at 544, 585, 610, 648, and 695 nm, corresponding to Tb 3+ 5 D4 → 7 F5 and Eu 3+ 5 D0 → 7 F1, 5 D0 → 7 F2, 5 D0 → 7 F3 and 5 D0 → 7 F4 transitions were observed. The PEDOT: PSS film has an enhancement effect on electroluminescence.